2016
DOI: 10.18632/oncotarget.9351
|View full text |Cite
|
Sign up to set email alerts
|

NRAS and EPHB6 mutation rates differ in metastatic melanomas of patients in the North Island versus South Island of New Zealand

Abstract: Melanoma, the most aggressive skin cancer type, is responsible for 75% of skin cancer related deaths worldwide. Given that New Zealand (NZ) has the world's highest melanoma incidence, we sought to determine the frequency of mutations in NZ melanomas in recurrently mutated genes. NZ melanomas were from localities distributed between North (35°S-42°S) and South Islands (41°S-47°S). A total of 529 melanomas were analyzed for BRAF exon 15 mutations by Sanger sequencing, and also by Sequenom MelaCarta MassARRAY. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In the search of additional potential initiator mutations in GNAQ/GNA11 wildtype tumors, we focused on the protein tyrosine kinase 2 beta (PTK2B) gene given the central role of PTK2B in many intracellular signaling cascades including mitogen activated (MAP)-kinase signaling [30] and the occurrence of mutations in CM including a hotspot in G414 [31,32,33]. In the dataset of Martin et al [11], we identified a G941D mutation in the PTK2B gene.…”
Section: Resultsmentioning
confidence: 99%
“…In the search of additional potential initiator mutations in GNAQ/GNA11 wildtype tumors, we focused on the protein tyrosine kinase 2 beta (PTK2B) gene given the central role of PTK2B in many intracellular signaling cascades including mitogen activated (MAP)-kinase signaling [30] and the occurrence of mutations in CM including a hotspot in G414 [31,32,33]. In the dataset of Martin et al [11], we identified a G941D mutation in the PTK2B gene.…”
Section: Resultsmentioning
confidence: 99%
“…Although enormous progress has been made in the successful treatment of advanced cutaneous melanoma using targeted therapy and immune checkpoint inhibitors, the response rates and outcomes in the setting of metastatic mucosal melanoma are less promising. In particular, there is very limited knowledge about the use of targeted therapies in the treatment of primary mucosal melanoma [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…BRAF mutations are the most common ( Fig . b ), present in 30–50 per cent of cutaneous melanomas, followed by NRAS (25 per cent) and NF1 (less than 10 per cent) mutations. All three strongly associate with genetic signatures of an ultraviolet (UV) radiation effect, whereas less than 30 per cent of melanomas lacking any of these mutations (triple wild‐type) show UV signatures.…”
Section: Genomic Basis For Advances In Systemic Therapymentioning
confidence: 99%
“…Immunohistochemistry can serve as a quick screen, with excellent sensitivity for the BRAF V600E mutation. If immunohistochemistry is negative, alternative forms of testing are required to screen for other treatable mutations in BRAF (such as V600K, present in 10–20 per cent of the BRAF ‐mutant melanoma population) and other genes. Assays using multiplex PCR can amplify multiple targets in one test.…”
Section: Genomic Testing To Guide Treatment Of Metastatic Diseasementioning
confidence: 99%